2018
DOI: 10.4149/bll_2018_057
|View full text |Cite
|
Sign up to set email alerts
|

Helicobacter pylori can be related to carotid intima-media thickness, epicardial adipose tissue thickness and serum neutrophil gelatinase-associated lipocalin (NGAL) levels

Abstract: HP-infection can lead to subclinical atherosclerosis via chronic inflammation. The higher the activity of HP infection, the higher the acceleration of atherosclerosis (Tab. 3, Fig. 2, Ref. 46). Text in PDF www.elis.sk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(19 citation statements)
references
References 39 publications
2
16
0
1
Order By: Relevance
“…In this survey, we investigated the relationship between Hp infection and CIMT in general subjects. Though numerous more recent publications concerning these associations are available 14 , 15 , our results were consistent with previous cohort studies that indicate no significant correlation between Hp infection and the average CIMT 13 .…”
Section: Discussionsupporting
confidence: 93%
“…In this survey, we investigated the relationship between Hp infection and CIMT in general subjects. Though numerous more recent publications concerning these associations are available 14 , 15 , our results were consistent with previous cohort studies that indicate no significant correlation between Hp infection and the average CIMT 13 .…”
Section: Discussionsupporting
confidence: 93%
“…Karadag et al studied CIMT, epicardial adipose tissue thickness, and biologic markers of inflammation in 90 dyspeptic patients, according to the presence of H pylori in gastric biopsies (Sydney classification) and found an independent association between gastric inflammation, H pylori infection, epicardial adipose tissue thickness, and CIMT. The latter was also independently associated with a high sensitivity C‐reactive protein level . A recent case‐control study performed by Kutluana et al showed that systemic arterial stiffness measured by pulse wave velocity was higher in patients with gastric intestinal metaplasia and atrophic gastritis, with lower B12 vitamin levels …”
Section: Cardiovascular Diseasesmentioning
confidence: 97%
“…By reading the consensus of experts, 12 the data in Judaki (2017) 21 are not consistent with it, so it was also excluded. Overall, a total of 24 pieces of literature were finally included, of which 14 were about CIMT, [21][22][23][24][25][26][27][28][29][30][31][32][33][34] 2 were about FMD, 35,36 and 9 were about PWV. 23,[37][38][39][40][41][42][43][44] In addition, four studies have reported the relationship between Helicobacter pylori cytotoxin-associated gene-A (CagA)-positive strains and CIMT.…”
Section: Literature Search Processmentioning
confidence: 99%